Saint Marks : Words, Images, and What Persists - Goldberg, Jonathan (Book collections on Project MUSE., 2018)
Saint Marks is a study based on the multiple representations of St. Mark, with a focus on Venetian Renaissance paintings and the gospel attributed to him, and theoretical work by philosophers and art historians who consider the afterlives of art works and our attachments to them. The life studied in this book is a materiality that exceeds human mortality.